Fertility after timed breeding using GnRH, PGF2, and norgestomet - Thompson, K. E.; Lamb, G.C.; Marple, T.J.; Corah, L.R.; McKee, R.M.; Stevenson, Jeffrey S.; Grieger, David M.; Nichols, David A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
At the KSU Purebred Unit, 164 purebred Angus, Hereford, and Simmental cows were used to test a new estrus-synchronization program using GnRH, PGF2, and norgestomet. Cows were inseminated after detected estrus, or in the absence of estrus, inseminations were made at one fixed time after a second injection of GnRH. The treatment consisted of a 100 µg injection of GnRH plus a 6-mg ear implant of norgestomet. Seven days later, the ear implant was removed, and 25-mg of PG F2% was injected. In the absence of estrus, the time-bred group received a second injection of GnRH 48 h after PGF2% and was inseminated 16 h later. The treatment induced 10 of 36 anestrous cows to ovulate. Conception rates tended (P<.09) to be greater in Angus (72.2%) than Hereford cows (52.8%) , with conception rates in Simmental cows (51.5%) being similar to those in Hereford. Overall, pregnancy rates were similar between the time-bred group (59.3%) and the estrus-bred group (53.8%). We conclude that using GnRH, PG F2%, and norgestomet in a timed breeding program ca n eliminate the necessity of heat detection. In addition, the treatment induced estrus in 28% of the noncycling cows.
Keywords: Beef; GnRH; PGF2; Norgestomet; Timed breeding; Anestrous suckled cows; Induced ovulation